Evaluasi Ketersediaan Koleksi dengan Menggunakan Analisis Sitiran Terhadap Tesis Mahasiswa Pascasarjana Program Studi Ilmu Biomedik Tahun 2012 di Perpustakaan Fakultas Kedokteran Universitas Andalas - Anggraini, Lusi; Nst., Bakhtaruddin (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This study aimed to describe the characteristics and availability of literature cited in the Biomedical Sciences Graduate Student Thesis of 2012 in the Library of the Medicine Faculty, Andalas university. This study is descriptive quantitative research that is the subject of the entire thesis, which has 21 theses. Object of research is all citations contained in the bibliography thesis studied. Data collection techniques used was documentation technique with the application of citation analysis methods. Instrument that used is secondary data. Data analysis is the data tabulated and analyzed based on the percentage and it presented in tabular form. The results showed that the characteristics of the cited literature that there are 19 types of literature with a total number of 848 citations. Kind of literature the most widely cited is a book that is 399 citations (47,05%). Title of literature that is often cited is the Journal of Nutrition 18 citations (2,12%). Author who often cited is Guyton about 10 citations (1,18%). The dominant language of literature cited is Indonesian, namely 451 citations (53,18%). Half life literature cited in the thesis is 9,37 years. The Percentage availability of the cited literature as a whole is 57,55% and 42,45% not available at the Library of the Medicine Faculty, Andalas University. Keywords: evaluate the colection; citation analysi; Â availability of literature